Artificial intelligence & digital ecosystems and their role in shaping the future of automotive aftersales - Raudies, Mona (2024)
This thesis examines the role of artificial intelligence (AI) and digital ecosystems (DEs) in shaping the future of the automotive aftersales domain. This research addresses a gap in the existing literature, which has predominantly focused on broader digital transformation trends, thereby leaving the specific implications for aftersales services underexplored. By employing a qualitative approach based on 11 semi-structured interviews with experts from the automotive and consulting sectors, the study identifies key use cases for AI and DE integration, including personalized customer experiences, AI-driven customer support chatbots, and predictive maintenance. Additionally, it explores the strategic role of aftersales DEs in enhancing the competitiveness of original equipment manufacturers (OEMs) by improving customer relationships, leveraging external skills and knowledge, and establishing entry barriers. Furthermore, the research identifies significant challenges in the integration process, including the harmonization of technology, data management and regulatory compliance. The study concludes with lessons learned for OEMs, emphasizing the importance of a holistic approach, workforce education and the need to balance technological innovation with humancentric strategies. Overall, the findings contribute both to the academic discourse and provide actionable recommendations for industry practitioners aiming to leverage AI and DEs in the rapidly evolving automotive aftersales sector.